INDONESIAN STUDENT TEACHERS’ ANXIETY DURING TEACHING PRACTICUM AT A PRIVATE SHS IN CENTRAL JAVA - Yohana Joifani Rambu Djawamara; Listyani Listyani (English Language Education Study Program Association (ELESPA) or Asosiasi Program Studi Pendidikan Bahasa Inggris (APSPBI), Indonesia, 2021)
Teaching practicum is a compulsory course for students majoring in education program. Through teaching practicum, student teachers can gain experiences before becoming real teachers. However, there are some students who still feel anxious towards teaching practicum. Therefore, this study aimed to find out the factors contributing to student teachers’ anxiety during teaching practicum and the strategies to cope with the anxiety. The participants of this study were six student teachers who had done their teaching practicum at a private senior high school in Central Java. The data were collected qualitatively by using semi-structured interviews to get in-depth information from the participants. The findings revealed that facing a new environment, school teachers and students’ attitudes, lesson plans and teaching materials, the ways of presenting the materials, time management, availability of AVAs, and observation by mentor teachers and the supervisor were the factors that contributed to student teachers’ anxiety during teaching practicum. The strategies used by student teachers to cope with their anxiety were adapting themselves with the new environment, preparing well before teaching, building good rapport with school teachers and students, creating a good learning environment, prioritizing the most crucial teaching part, and doing relaxation.